PERLINDUNGAN HUKUM PENGGUNA KREDIT YANG IDENTITASNYA DIGUNAKAN ORANG LAIN DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 8 TAHUN 1999 - Agustri Purwandi (Yos Soedarso Economic Journal (YEJ), 2021)
Humans are social creatures, which means that humans like to hang out and live in groups, so that in this relationship the identity of each individual or group facilitates relationships. Not only that, identity has an important role for the continuation of an agreement, with identity, the parties can know and know each other so that the agreement to be agreed is carried out properly. Especially for credit agreements where identity is the main condition that becomes the reference for receiving credit applications. The agreement that has been carried out and reached the agreement is valid as a law for the parties making it, so that in the legal relationship there are rights and obligations to be fulfilled and protected by each other. The purpose of this research is to find out how the legal protection of credit users whose identities are used by others and to find out the legal strength of the agreements that have been agreed by the parties before the credit is granted. This writing is done by examining primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of this writing, a person whose identity has been borrowed to get credit is entitled to his rights according to the provisions of the Consumer Protection Law in article 4 because the owner of the identity is listed as a consumer in a banking institution after the agreement is signed which is legally binding in accordance with Article 1338 of the Criminal Code, if that declare that the agreement is not under pressure or incitement from other parties, so that the agreement does not violate decency, public order and law.Keywords: Legal Protection; Credit Users; Identity.